Facilitators and Barriers to Health Care Access among the Elderly in Tanzania: A Health System Perspective from Managers and Service Providers. - Frumence, Gasto; Nyamhanga, Tumaini; Anaeli, Amani (Journal Of Aging Research And Healthcare, 2017)
Tanzania is among the developing countries experiencing rapid growth of an ageing population, which has an implication in healthcare expenditure especially in resource poor settings where majority of elderly people cannot afford to pay for the cost of accessing health services. The country has developed the Tanzania National Health Policy (2007) and National Ageing Policy (2003), which, among other things, recognize the importance of having a healthcare system that provides free basic services to the vulnerable elderly population. This study aimed at exploring health service providers’ and managers’ perspectives on the factors facilitating or prohibiting access to health services among elderly people in Tanzania. The study adopted a qualitative approach and data were collected using semi-structured interviews. A total of 24 in-depth interviews were conducted with district healthcare managers, heads of public healthcare facilities, and health service providers. The data generated were analysed for themes and patterns. The results show that Tanzania’s healthcare system has made some efforts to implement the national exemption policy to ensure better access to health services for the elderly. Some of these efforts include: having in place a system to identify and exempt elderly people from paying for health services and giving them special priority during treatment. However, there are some barriers hindering elderly people’s access to health services. Among others include: lack of specific consultation rooms and doctors for serving the elderly, and lack of sufficient drugs and other medical equipment in most government-owned healthcare facilities. In summary, the healthcare system has created a good environment for the implementation of exemption policy aiming at enhancing accessibility of health services among the elderly population in the country. However, such environment cannot function effectively without addressing the identified barriers. It is recommended that the government should allocate adequate human and non-human resources to the healthcare system to enable it to function effectively, including the provision of health services to the elderly.
Keywords: elderly; access; health services; health system; Tanzania